INSTITUTIONAL DISCONNECT IN CHARACTER EDUCATION: A CASE STUDY OF PUBLIC ELEMENTARY SCHOOLS IN YOGYAKARTA - Izzul Kiram Suardi; Muhammad Nursa'ban; Uldiyanti Sya’diah Syahdan (Jurnal Suluh Pendidikan, 2026)
The implementation of character education during the early transition phase in urban elementary schools encounters significant structural barriers. This study aims to map and analyze the network of operational constraints affecting character education programs in five public elementary schools in Yogyakarta City. A qualitative case study methodology was employed, utilizing in-depth interviews with 16 purposively selected informants, including principals, coordinators, and teachers. Thematic coding was applied to visualize causal relationships among the identified issues using ATLAS.ti software facilitating data analysis. The results reveal five principal clusters of constraints: environment, parents, program, students, and teachers. At the macro level, urban social inequality and parental dysfunction, such as neglect and denial, contribute to behavioral crises among students. Structural ambiguity within curriculum modules leads to operational confusion. The accumulation of these challenges creates a dual burden and systemic burnout among educators, hindering their emotional engagement in the classroom. In conclusion, the inability to instill ethical values in young children is attributed not to pedagogical shortcomings but to broader ecological dysfunction. The findings recommend implementing structured psychoeducation for parents and developing assessment instruments aligned with children's psychological development.